Effects of Protective Lacticaseibacillus casei VC201 Culture on Late Blowing Prevention, Lipid Profile, and Sensory Characteristics of Valtellina Casera PDO Cheese During Ripening - Francesca Bonazza; Stefano Morandi; Tiziana Silvetti; Alberto Tamburini; Ivano De Noni; Fabio Masotti; Milena Brasca (Foods, 2025)
This study aimed to verify, under real operating conditions, the effectiveness of protective lactic acid bacteria (LAB) culture in counteracting the development of late blowing defects in Valtellina Casera PDO cheese and its impact on product sensory characteristics. Thirty-four LAB isolated from Bitto and Valtellina Casera PDO cheeses were screened for anti-Clostridium activity. Lacticaseibacillus casei VC201 was able to inhibit all the indicator strains through organic acid production. Valtellina Casera PDO cheese-making was performed twice in three dairy farms using a commercial autochthonous starter culture with and without the addition of the protective culture VC201. Cheese was ripened both at 8 °C and 12 °C and analyzed after 70 and 180 days for LAB population, proteolysis, and lipolysis evolution as well as sensory impact. Cheeses with the addition of the VC201 strain showed higher contents of rod-shaped LAB throughout the ripening at both temperatures. The protective culture decreased the production of butyric acid at 70 days, especially at 8 °C (−15.4%), while butyric fermentation was occasionally lightly observed at 12 °C. The sensory profile was favorably impacted by the higher relative proportion of short-chain fatty acids (SCFFAs, C2–C8), which was especially pronounced at 8 °C and persisted for 180-day ripening (23.91% vs. 18.84% at 70 days and 23.84 vs. 21.71 at 180 days of ripening). The temperature and time of ripening had a significant effect on the free fatty acid content of the cheese samples in all three classes (SCFFA, MCFFA, and LCFFA). The cheese made with Lcb. casei VC201 was preferred, according to the sensory evaluation, being perceived as less acidic, less bitter, tastier, and with more intense flavor. Protective cultures can represent a practical way to reduce late blowing defects in Valtellina Casera cheese production while maintaining adherence to its PDO regulatory requirements.